Profil Suhu dan Kadar Air Kayu dalam Pengeringan Oven Pemanas dan Gelombang Mikro (Temperature and Moisture Content Profiles of Woods in Heating and Microwave Ovens Drying) - Trisna Priadi; Gunes T W Giyarto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2019)
This research aimed to evaluate the profile of temperature and moisture content in Pinus oocarpa wood being dried with heating oven and microwave oven.  The size of samples were (25x70x120) mm3.  The temperature profiles in heating oven and microwave oven drying were taken every 10 minutes and 0.5 minutes, respectively. The moisture profiles in heating oven and microwave oven drying were made in every 24 hours and 10 minutes, respectively.  The heating oven was set at 60 °C, while microwave oven was set for 2 minutes intermittently with 5 minutes break.  In microwave drying, the temperature inside the boards increased faster and higher compared to that in the heating oven, which resulted in a faster moisture movement to the board’s surface.  The drying rate of pine increased 48-72 times in microwave compared to that in heating oven.  The moisture content in the centre of boards being dried in heating oven was much higher than that of in the outer parts.  On the other hand, the moisture profile in the woods being dried in microwave oven distributed more evenly.